HASIL BELAJAR KETERAMPILAN PSIKOMOTOR FISIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TPS DAN TSTS PADA SISWA KELAS X MA DAR EL HIKMAH PEKANBARU - Zulirfan Zulirfan; Diana Diana; Mitri Irianti (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2009)
This research aim to find the differences between the results of learning psychomotor skills ofphysics students to the concept of straight-line motion in the X class students MA Dar El Hikmahpekabaru between cooperative learning Think-Pair-Square and Two Stay Two Stray. This researchis the research study design experiments with the Posttest-Only Control Design. XB1-class researchsample as a class experiment I with the application of cooperative learning model Think-Pair-Square and class XB2 as a class experiment II with the application of cooperative learning TwoStay Two Sstray. Instrument data collection in this research are to learn psychomotor test resultsare analyzed by descriptive analysis and inferential analysis. Deskritif analysis obtained from theexperimental class I absorption average is 84.6% of students with a good category, exhaustivenessclassical learning students with 87.5% complete and exhaustiveness category subject matter is100% with complete categories. In the experimental class II absorption average is 85.9% ofstudents with a good category, effektiveness lesson is 85.9% with effective category, theexhaustiveness of students to study classical category of 91.6% with complete and completeness oflearning material is 100% by category thoroughly. With inferential after the data obtained arenormally distributed and homogeneous through the test for normality and homogenity test resultsobtained that the hypothetical accept, so there is no difference significan on student learningoutcomes through learning model Think-Pair-Square and Two Stay Two Stray. This can be seenthrough the t test was called t calculated <t table or 0.515 <1.679 by SPSS version 16.